Effects of Echinacea purpurea and Alkylamides on Respiratory Virus Replication and IL-8 Expression In Vitro - Keely Puchalski; Johanne A. Gerstel; Abiola Jimoh; Yalda Shokoohinia; Jeffrey Langland (Molecules)
Echinacea purpurea is a perennial medicinal herb with important immunomodulatory and anti-inflammatory properties, especially purported for the alleviation of cold and flu symptoms. Different classes of secondary metabolites of the plant, such as alkylamides, caffeic acid derivatives, polysaccharides, flavonoids, and glycoproteins, are believed to be biologically and pharmacologically active. Although previous research suggests that the alkylamides present in Echinacea may be responsible for reducing the symptoms associated with the common cold or flu through their immunomodulatory activity, the roles of specific alkylamides and their targets (i.e., immune and/or antiviral) have not been well-elucidated or established. This study tested the antiviral and cytokine regulatory activity of various specific alkylamides that are present predominantly in Echinacea root extracts and found that one specific alkylamide, Dodeca-2E,4E-Dienoic acid isobutylamide, had potent antiviral activity against rhinovirus (the causative agent of most common colds) and influenza virus, as well as potent inhibition of IL-8 cytokine production. IL-8 is responsible for many of the symptoms associated with the common cold and is upregulated in other common respiratory infections. The broad activity and low cytotoxicity of this specific alkylamide support its potential use for treating rhinovirus and influenza virus infections.